Responsiveness of the Regional Public Drinking Water Companies Tirta Lestari in Providing Public Services in Tuban Regency - Rahmawati, Viona Eka Rahmawati; Widiyarta, Agus (Journal La Sociale, 2024)
One of the institutions that has the authority to carry out public services and provide services in terms of providing clean water is the Regional Public Drinking Water Companies in the form of Regional Public Companies. As a form of fulfilling the right to clean and healthy water as a human right, Regional Public Drinking Water Companies are responsible for facilitating and providing clean water services for the community. This research aims to describe the responsiveness of public services at the Regional Public Drinking Water Companies Tirta Lestari, Tuban Regency. The type of research used is descriptive qualitative. Data collection techniques through observation, interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions or verification. The theory used is the Responsiveness theory from Zeithaml in Hardiansyah (2018) which consists of the ability to respond to each customer, speed of service, accuracy of service, accuracy of officers, timeliness of service, and officers responding to customer complaints. The research results show that the services provided at the Tirta Lestari Regional Drinking Water Company, Tuban Regency have shown responsive service and customers have received service according to responsiveness indicators. However, there are still obstacles in the service delivery process.